Hubungan Praktik Penggunaan Insektisida dengan Kejadian Demam Berdarah Dengue di Semarang - Dyah Ayu Riani; Nur Endah Wahyuningsih; Anto Budiharjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by one of 4 different Dengue virus and transmitted through Aedes aegypti and Aedes albopictus mosquitoes. DHF is one of the major public health problems in Indonesia, one of which is in Semarang and its surroundings. Incidence Rate (IR) DHF of Semarang District from 2006 to 2016 is always much higher than IR DHF Central Java and IR DHF National. This study aims to analyze the practice of insecticide use with the incidence of DHF in Semarang. The type of research used is observational analytic done with case control approach. The population in this study were DHF in March-May 2017 at three hospitals in Semarang City and not DHF (neighbor patient) who live in Semarang and surrounding areas (Kendal and Demak). The sample was 48 cases and 48 controls using consecutive sampling technique. Data obtained in this study were analyzed by Chi-Square test and calculation of Odds Ratio with 95% confidence interval. The results showed that there was no correlation between the use of insecticide (p=0,289, OR=0,636 and 95% CI=0,275-1,471). Based on these results, the practice of insecticide use is not related to the incidence of DHF in Semarang. Therefore, people are expected to always apply healthy hygiene behavior and do 3M Plus in order to avoid the incidence of DHF.